2018
DOI: 10.3390/microorganisms6030093
|View full text |Cite
|
Sign up to set email alerts
|

Thermostable Xylanase Production by Geobacillus sp. Strain DUSELR13, and Its Application in Ethanol Production with Lignocellulosic Biomass

Abstract: The aim of the current study was to optimize the production of xylanase, and its application for ethanol production using the lignocellulosic biomass. A highly thermostable crude xylanase was obtained from the Geobacillus sp. strain DUSELR13 isolated from the deep biosphere of Homestake gold mine, Lead, SD. Geobacillus sp. strain DUSELR13 produced 6 U/mL of the xylanase with the beechwood xylan. The xylanase production was improved following the optimization studies, with one factor at a time approach, from 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 52 publications
0
39
0
Order By: Relevance
“…The requirement of these nitrogen sources varies for different microorganisms; therefore, optimizing the type and level of nitrogen source in the media is an important parameter (Seyis and Aksoz 2005;Naveen et al 2014;Irfan et al 2016). Trace elements, amino acids, and vitamins are also important parameters for the growth of different microorganisms (Simair et al 2010;Bibra et al 2018). Therefore, regulating their levels in the media is important for regulating the production of xylanase.…”
Section: Role Of Important Media Components Used For Xylanase Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…The requirement of these nitrogen sources varies for different microorganisms; therefore, optimizing the type and level of nitrogen source in the media is an important parameter (Seyis and Aksoz 2005;Naveen et al 2014;Irfan et al 2016). Trace elements, amino acids, and vitamins are also important parameters for the growth of different microorganisms (Simair et al 2010;Bibra et al 2018). Therefore, regulating their levels in the media is important for regulating the production of xylanase.…”
Section: Role Of Important Media Components Used For Xylanase Productionmentioning
confidence: 99%
“…These strategies resulted in an enhancement in reaction rates and ethanol yields (Eklund and Zacchi 1995;Sun and Cheng 2002). Bibra et al (2018) showed thermostable xylanase production using Geobacillus sp. DUSELR13, which is applied further for ethanol generation from LCB.…”
Section: Xylanase Employed In Biorefinerymentioning
confidence: 99%
“…WSUCEF1 isolated from soil and Geobacillus sp. DUSELR 13 isolated from the deep gold mines of South Dakota [49,50]. Xylanase from Geobacillus sp.…”
Section: Xylanase and β-Xylosidasementioning
confidence: 99%
“…WSUCEF1 showed a half-life of 18 days and 12 days at 60 • C and 70 • C, respectively, while Geobacillus sp. DUSELR 13 produced 31 U/mL after optimization and exhibited a half-life of 13 days at 60 • C and 70 • C [49,50].…”
Section: Xylanase and β-Xylosidasementioning
confidence: 99%
See 1 more Smart Citation